Construction of indicator system of tourism professional skills evaluation system in the application-oriented Universities - A case study in Fujian, China - Hung-Lung Lin; Xiang Li; Jia-Min Zhang (PLoS ONE, 2025)
This study aims to establish a “Tourism Professional Skills Evaluation System in Application-Oriented Universities” to bridge the gap between industry requirements and traditional curricula. In response to the tourism sector’s rapid growth and shifting market demands, this study employ the Modified Delphi Method (MDM) and Analytic Hierarchy Process (AHP) to identify and weight five core competency domains: basic professional knowledge and skills, professional related knowledge and skills, interpersonal and self-development skills, physical fitness, as well as cultural and ethical rule of ethics qualities. Through expert panels and group discussions, this study develops a comprehensive set of indicators covering all essential competencies. The system has been piloted at a case university and received strong endorsement from both industry and academic stakeholders. By quantitatively defining indicator hierarchies and weights, this framework delivers a scientifically grounded, objective tool for educators, administrators, and policymakers to design and refine tourism talent development programs.